निम्नलिखित को सरल कीजिए।
\dfrac{(8.3)^3+(9.2)^3+(6.1)^3-3 \times 8.3 \times 9.2 \times 6.1}{(8.3)^3+(9.2)^3+(6.1)^3- 8.3 \times 9.2 - 9.2 \times 6.1 - 6.1}

Options
a) 25.5
b) 30.2
c) 28.7
d) 23.6

Solution

\dfrac{(8.3)^3+(9.2)^3+(6.1)^3-3 \times 8.3 \times 9.2 \times 6.1}{(8.3)^3+(9.2)^3+(6.1)^3- 8.3 \times 9.2 - 9.2 \times 6.1 - 6.1}
सवाल को निकलने के लिए माना:
8.3 =a
9.2 = b
6.1 = c

\dfrac{a^3+b^3+c^3-3abc}{a^2+b^2+c^2-ab-bc-ca}
Formula: a3+b3+c3-3abc = (a+b+c) (a2+b2+c2-ab-bc-ca)
\dfrac{(a+b+c) (a^2+b^2+c^2-ab-bc-ca)}{(a^2+b^2+c^2-ab-bc-ca)} = (a+b+c)
Put value in (a+b+c)
(8.3+9.2+6.1) = 23.6

Answer = 23.6

Scroll to Top